Chitinase 3 like 1 is a regulator of smooth muscle cell physiology and atherosclerotic lesion stability. Issue 14 (7th February 2021) - Tsantilas, Pavlos; Lao, Shen; Wu, Zhiyuan; Eberhard, Anne; Winski, Greg; Vaerst, Monika; Nanda, Vivek; Wang, Ying; Kojima, Yoko; Ye, Jianqin; Flores, Alyssa; Jarr, Kai-Uwe; et al.
Abstract: Aims : Atherosclerotic cerebrovascular disease underlies the majority of ischaemic strokes and is a major cause of death and disability. While plaque burden is a predictor of adverse outcomes, plaque vulnerability is increasingly recognized as a driver of lesion rupture and risk for clinical events. Defining the molecular regulators of carotid instability could inform the development of new biomarkers and/or translational targets for at-risk individuals. Methods and results : Using two independent human endarterectomy biobanks, we found that the understudied glycoprotein, chitinase 3 like 1 ( CHI3L1 ), is up-regulated in patients with carotid disease compared to healthy controls. Further, CHI3L1 levels were found to stratify individuals based on symptomatology and histopathological evidence of an unstable fibrous cap. Gain- and loss-of-function studies in cultured human carotid artery smooth muscle cells (SMCs) showed that CHI3L1 prevents a number of maladaptive changes in that cell type, including phenotype switching towards a synthetic and hyperproliferative state. Using two murine models of carotid remodelling and lesion vulnerability, we found that knockdown of Chil1 resulted in larger neointimal lesions comprised by de-differentiated SMCs that failed to invest within and stabilize the fibrous cap. Exploratory mechanistic studies identified alterations in potential downstream regulatory genes, including large tumour suppressor kinase 2 ( LATS2), which mediates macrophage marker and inflammatory cytokine expression on SMCs, and may explain how CHI3L1 modulates cellular plasticity. Conclusion : CHI3L1 is up-regulated in humans with carotid artery disease and appears to be a strong mediator of plaque vulnerability. Mechanistic studies suggest this change may be a context-dependent adaptive response meant to maintain vascular SMCs in a differentiated state and to prevent rupture of the fibrous cap. Part of this effect may be mediated through downstream suppression of LATS2. Future studies should determine how these changes occur at the molecular level, and whether this gene can be targeted as a novel translational therapy for subjects at risk of stroke. Graphical Abstract: